Inherited non-invertible duality symmetries in quiver SCFTs - Riccardo Argurio; Andrés Collinucci; Salvo Mancani; Shani Meynet; Louan Mol; Valdo Tatitscheff (Journal of High Energy Physics, 2025)
Abstract We revisit the construction of the duality group for $$\mathcal{N}$$ = 2 $${\widehat{A}}_{n}$$ -shaped quivers SCFTs and generalize it to the previously unexplored case of $${\widehat{D}}_{n}$$ -shaped quivers. We then provide a systematic description of non-invertible duality symmetries in both classes. Furthermore, we characterize the $$\mathcal{N}$$ = 1 mass deformations of these theories that preserve such symmetries, thereby identifying a large class of $$\mathcal{N}$$ = 1 SCFTs with non-invertible duality symmetries inherited from their parent $$\mathcal{N}$$ = 2 theories.